PENGARUH MEDIA SOSIAL TERHADAP PERILAKU KONSUMTIF MAHASISWA DALAM PENGELOLAAN KEUANGAN PRIBADI - Samuel Bagus Kristiawan; Aris Eddy Sarwono (Lembaga Pengembangan Kinerja Dosen, 2025)
Abstract. This study examines the influence of social media on student consumer behavior in managing personal finances. It aims to identify the role of advertising exposure, influencers, and social interaction in shaping consumption decisions. Using a quantitative survey approach with 100 students in Surakarta, the findings suggest that social media significantly affects spending behavior and financial management.